360 The Ability of an Enhanced Zeolite-Based Flow Agent to Mitigate the Effects of Ergot-Like Alkaloids Consumed by Beef Cattle. (21st September 2022) - Zeltwanger, Joshua M; Bailey, Eric; Hergenreder, Jerilyn; Canterbury, Landon; Brake, Derek; Petzel, Emily; Nelson, Benjamin; Du Xiangwei,; Evans, Tim
Abstract: Aluminosilicate-based flow agents, like zeolites, may impact digestion of ergot-like alkaloids in the ruminant gut. Twenty-four steers (226 ± 27.6 kg) were used in a 21-d experiment to test the effects of an enhanced zeolite-based flow agent (KALLSIL, Kemin Industries, Des Moines, IA) on site of ergot-like alkaloid excretion, serum prolactin, rectal temperature, respiration rate, and nutrient digestibility. Treatments were control (E+) or enhanced zeolite inclusion (E+Z; 2 g/kg, DM basis). Steers were fed a TMR at 1.85% of BW (DM-basis). Tall-fescue seed was included in the diet at 11.14%, providing 465 µg of ergovaline/kg DM. Steers had no ORTS during the experiment. Rectal temperature and respiration rate were recorded daily at 0700 and 1200 h from steers housed tie stalls in a room kept at (18.5°C ± 0.33°C, 32.6% ± 2.19%). Serum was harvested from blood collected on d-1, 7, 14, and 21 to measure prolactin. On d-21 jugular catheters were placed to measure prolactin following the infusion of thyrotropin-releasing hormone (TRH; 1 µg/kg BW). Spot samples of feces and urine were collected every 8 h from d 17-20, with 2-hour advancement each day to determine digestibility, N balance, and recovery of ergot-like alkaloids. Digestion and N balance was not affected by treatment (P ≥ 0.16). Enhanced zeolite tended (P = 0.15) to increase recovery of ergovaline. Prolactin concentration decreased over time (P < 0.01), but was greater (P = 0.01) at each time point for E+Z steers. Following the infusion of TRH, prolactin tended (P = 0.11) to be greater for E+Z. Rectal temperatures and respiration rates were not affected (P ≥ 0.89) by E+Z. Results from this study indicate that enhanced zeolite inclusion tended to increase recovery of ergot-like alkaloids in feces and increased serum prolactin when offered to beef steers in a diet containing ergot-like alkaloids.